Comparative Study Kinerja dengan Balanced Scorecard Puskesmas Terakreditasi & Terimplementasi ISO 9001: 2008 di Puskesmas Cilandak Timur & Pejaten Barat III - Desrialita Faryanti; Hermawan Saputra; Aragar Putri (Jurnal Health Sains, 2022)
This research was to conduct a comparative study of working performance with balanced scorecard in accredited and ISO certified health center. Used descriptive mix method with cross-sectional approach by purposive sampling method. The financial perspective of the two health centers have the same regulation, namely that finance is directly managed by sub-district (higher) health center. The mix income was obtained from general income and national health insurance capitation. The claims directly goes into the account of the sub-district health center, while general income is at general insert fee of Rp.2000. The perspective of health center customers related to accredited health center is 80% satisfied, 100% retention, ISO certified health center is 80% satisfied, 60% retention. Internal business perspective of accredited health center: children's playground and planning of special calling list for blind patients, ASI corner, ISO certified health centers have stimulation of toddler development and TB cadres. The perspective of learning growth in ISO certified health center is better than accredited health center. Suggested for health center to improve the working performance by proposing additional staff. For academics, it is hoped to add more literature related to health policy in Indonesia. For the next researcher, adding unexisted factors